2021
DOI: 10.1186/s41021-021-00228-9
|View full text |Cite
|
Sign up to set email alerts
|

A DNA adductome analysis revealed a reduction in the global level of C5-hydroxymethyl-2′-deoxycytidine in the non-tumoral upper urinary tract mucosa of urothelial carcinoma patients

Abstract: Background DNA adducts, covalent modifications to DNA due to exposure to specific carcinogens, cause the mispairing of DNA bases, which ultimately results in DNA mutations. DNA methylation in the promoter region, another type of DNA base modification, alters the DNA transcription process, and has been implicated in carcinogenesis in humans due to the down-regulation of tumor suppressor genes. Difficulties are associated with demonstrating the existence of DNA adducts or chemically modified base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…However, the levels of these oxidative adducts were not significantly different between medulla-RCC and non-RCC patients or between pelvis-UTUC and pelvis-non-UTUC groups. 26 In the same study, investigators reported a reduction in the global level of 5-hydroxymethyl-2′-deoxycytidine in the nontumoral urinary tract mucosa of urothelial carcinoma patients, which may impact epigenetic events in renal cancer development.…”
Section: ■ Introductionmentioning
confidence: 95%
“…However, the levels of these oxidative adducts were not significantly different between medulla-RCC and non-RCC patients or between pelvis-UTUC and pelvis-non-UTUC groups. 26 In the same study, investigators reported a reduction in the global level of 5-hydroxymethyl-2′-deoxycytidine in the nontumoral urinary tract mucosa of urothelial carcinoma patients, which may impact epigenetic events in renal cancer development.…”
Section: ■ Introductionmentioning
confidence: 95%
“…Wang et al reported that deoxyinosine could be the biomarker to differentiate bladder cancer and kidney cancer patients from healthy people (24). Additionally, the deoxyinosine analog, C5hydroxymethyl-2′-deoxycytidine (5hmdC), is considerably decreased in the renal pelvis of UC patients (25).…”
Section: Ucs Vs Healthy Controlsmentioning
confidence: 99%
“…The incidence of AA‐induced nephropathy (AAN) is not limited to any specific geographic region and cases occur regularly throughout the world, despite warnings from many health agencies. Kidney injury and fibrosis are predictable features of AAN, such that it is now used as a kidney injury/fibrosis model in vitro and in vivo studies 11–13 . Although studies have provided considerable insights into mechanisms of AA‐induced nephropathy, the pathophysiology of AAN remains incompletely understood 14–19 …”
Section: Introductionmentioning
confidence: 99%
“…Kidney injury and fibrosis are predictable features of AAN, such that it is now used as a kidney injury/fibrosis model in vitro and in vivo studies. 11 , 12 , 13 Although studies have provided considerable insights into mechanisms of AA‐induced nephropathy, the pathophysiology of AAN remains incompletely understood. 14 , 15 , 16 , 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation